2012
DOI: 10.1111/j.1469-8986.2011.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of meal content on heart rate variability and cardiovascular reactivity to mental stress

Abstract: Little is known about transient effects of foods and nutrients on reactivity to mental stress. In a randomized crossover study of healthy adults (n = 20), we measured heart rate variability (respiratory sinus arrhythmia), blood pressure, and other hemodynamic variables after three test meals varying in type and amount of fat. Measurements were collected at rest and during speech and cold pressor tasks. There were significant post-meal changes in resting diastolic blood pressure (−4%), cardiac output (+18%), to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 82 publications
4
19
0
Order By: Relevance
“…These findings are in agreement with a previous study in which SBP, DBP, and TPR reactivity to a stress task were not influenced by meals that were either low in fat or high in saturated or polyunsaturated fat (Sauder et al 2012) (speech and cold pressor task, ϳ2.5 h postmeal), but are in contrast with other previous findings that blood pressure (Faulk and Bartholomew 2012;Jakulj et al 2007) and TPR (Jakulj et al 2007) reactivity were greater in response to laboratory stressors presented 2 h following consumption of an HFM versus a LFM. The reason for these disparate findings is unclear as all studies used similar subject populations (young, healthy adults), stress tasks (variations of speech tasks, mental arithmetic, and cold-pressor/ ischemia) and quantities of fat (ϳ40-54 g).…”
Section: Acute Interaction Between Meal Fat Content and Stress Responsupporting
confidence: 95%
See 2 more Smart Citations
“…These findings are in agreement with a previous study in which SBP, DBP, and TPR reactivity to a stress task were not influenced by meals that were either low in fat or high in saturated or polyunsaturated fat (Sauder et al 2012) (speech and cold pressor task, ϳ2.5 h postmeal), but are in contrast with other previous findings that blood pressure (Faulk and Bartholomew 2012;Jakulj et al 2007) and TPR (Jakulj et al 2007) reactivity were greater in response to laboratory stressors presented 2 h following consumption of an HFM versus a LFM. The reason for these disparate findings is unclear as all studies used similar subject populations (young, healthy adults), stress tasks (variations of speech tasks, mental arithmetic, and cold-pressor/ ischemia) and quantities of fat (ϳ40-54 g).…”
Section: Acute Interaction Between Meal Fat Content and Stress Responsupporting
confidence: 95%
“…While the anticipated postprandial changes in triglycerides, glucose, and insulin did occur (Table 2), they did not appear to moderate postprandial stress responses. The magnitude of postprandial lipemia in this study was similar to that in the previous study in which no impact of fat consumption on stress reactivity was observed (Sauder et al 2012).…”
Section: Time Course Of the Postprandial Responsesupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the communication between the vagus and ICC is bidirectional in that the vagal afferent fibers have synapse-like contact with ICC [20,21]. Our observation that the meal induced an increase in heart rate, consistent with findings in another recent study [22], could also the result of a meal-induced increase in sympathetic activity.…”
Section: Discussionsupporting
confidence: 81%
“…The LF parameter primarily reflects sympathetic activity, the HF parameter reflects parasympathetic activity, the TP parameter reveals overall autonomic activity, 19 and the LF/HF ratio represents sympathovagal balance or the complex interactions between the sympathetic and parasympathetic inputs. 20 The Shapiro-Wilks Normality Test revealed that all HRV parameters were highly skewed, as is typical of HRV studies [21][22][23][24] ; hence the derived HRV measures were natural logarithm transformed prior to analysis.…”
Section: Ecg Data Processingmentioning
confidence: 99%